Economic analysis of variable speed drive control through profinet technology on distributed control system: A case study in essential oil processing factories - Alim, Adhipa Tri Setyawan; Sudiarto, Budi (Universitas Negeri Padang, 2023)
Electrical equipment in essential oil processing plants is generally dominated by electric motor loads. In today's digital era, global competition and technological advances encourage factories to increase the efficiency and reliability of their production equipment. One way of efficiency is to use a variable speed drive (VSD). The existence of Profinet technology as a network protocol between the control equipment and the VSD allows users to increase system reliability while increasing energy use efficiency. Even so, there are still many factories that are hesitant to use this technology in their automation systems. Many low to medium-sized factories still use traditional control methods such as hardwired. This method is considered more reliable, and inexpensive compared to using Profinet technology. Cost-benefit analysis is carried out to prove this paradigm. At the same time provides certainty that the investment costs incurred in building the system provide added value for production equipment. From this research, it is proven that the use of Profinet technology in addition to providing savings on investment costs also provides benefits from a technical perspective. This technology also allows the implementation of condition-based monitoring systems for electric motors in production equipment. Which in turn can increase the performance and service life of the machine.